Analisis Efektifitas Penggunaan Layanan Koleksi Digital pada Perpustakaan Universitas Islam Negeri Sumatera Utara - Elisa, Mona; Yasmin, Nabila (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
The Islamic University of North Sumatra (UINSU) Library has transitioned to a digital library to meet the literacy and information needs of its students. This study aims to evaluate how well the digital collection services at UINSU Library meet user needs and identify the main challenges faced. The research employs a qualitative approach, using data collection techniques such as direct interviews and questionnaires. Data analysis is conducted through descriptive analysis methods to determine the effectiveness, barriers, and user satisfaction with the digital collection services at UINSU. The results indicate that the digital collection services are effective in facilitating information access. Overall, users express satisfaction with the ease of access and the wide availability of digital collections. However, users still encounter technical issues, such as slow internet connections with speeds of 2.4 GHz, which affect their information search experience. The study highlights the importance of managing technology and infrastructure adequately to support the library’s digital transformation towards more effective and responsive services to user needs in the digital age. The study concludes that this service provides significant benefits to users scattered across various locations, allowing them to access library collections without having to visit the library in person. Based on the informants' experiences using the service, there are numerous types of digital collections available in the library